Perception of the Use of Quizizz as an Evaluation Media in Japanese Language Learning at SMA Negeri 2 Batang Anai - Aufa Karen Sapphira; Rahmi Oktayory Wikarya (Omiyage : Jurnal Bahasa dan Pembelajaran Bahasa Jepang, 2026)
This study was motivated by the fact that many teachers still use conventional methods in the evaluation process, causing students to perceive evaluation activities merely as tasks to fulfill academic requirements. This study aimed to determine students' perceptions of the use of Quizizz as an evaluation medium in Japanese language learning at SMA Negeri 2 Batang Anai. The research employed a descriptive quantitative method, with data collected through questionnaires. The sample consisted of 64 students from Grade XII Advanced Phase F, specifically from classes XII F2 and XII F3. The results showed that the use of Quizizz as an evaluation medium in Japanese language learning obtained a mean score of 84.12 with a percentage of 94.4%, which falls into the positive category. These findings indicate that students responded positively to the use of Quizizz because it was considered engaging, practical, and supportive of the learning evaluation process. Therefore, it can be concluded that Quizizz can be used as an effective evaluation medium in Japanese language learning at SMA Negeri 2 Batang Anai.